POI after chemotherapy and bone marrow transplant may mimic disorders of sexual differentiation – a case report of a patient with primary amenorrhea and 46, XY karyotype. (2nd June 2020) - Kruszewska, Jagoda; Krzywdzińska, Sandra; Grymowicz, Monika; Smolarczyk, Roman; Meczekalski, Blazej
Abstract: Cytogenetic examination may be useful in determining the reason for primary amenorrhea in phenotypically female patients. The result 46, XY usually indicates two syndromes: complete androgen insensitivity or pure gonadal dysgenesis. We report a case of a patient, who due to acute lymphoblastic leukemia in childhood was treated with total body irradiation and bone marrow transplantation. Later on the patient presented with symptoms typical for premature ovarian failure and male karyotype in peripheral lymphocytes. The cytogenetic examination for peripheral cells showed normal female karyotype. Therefore, it has been concluded that ovarian function impairment resulted rather from the gonadotoxic effect of oncological treatment than as a disorder of sexual differentiation. The survival rates of childhood cancer are very high and some of the patients will experience premature ovarian failure. It must be remembered that after bone marrow transplantation karyotype of peripheral lymphocytes may be misleading.